Extraction and characterization of microfibrillated and nanofibrillated cellulose from office paper waste = Pengekstrakan dan pencirian mikrofibril dan nanofibril selulosa daripada sisa kertas pejabat - Md Hanafiah, Siti Fatimah; Danial, Wan Hazman; Abu Samah, Mohd Armi; Samad, Wan Zurina; Darnis, Deny Susanti; Mohd Salim, Rosliza; Abdul Majid, Zaiton (Malaysian Society of Analytical Sciences, 2019)
The tremendous increase in papermaking and cellulose production, both of which are sourced from wood pulp, has resulted in the severe exploitation of trees, thereby leading to environmental problems, including deforestation. Besides, the reduction of paper usage is not on the horizon. Thus, when it comes to the environmental issue, the extraction of cellulose from paper waste can be an alternative initiative to mitigate the negative impact of deforestation via the reuse of paper waste. In this study, the extraction of cellulose microfibres and nanofibres was achieved through the use of office paper waste as the source material. Alkali and bleaching treatments were employed for the extraction of cellulose fibres, followed by acid hydrolysis under controlled conditions for the isolation of the cellulose nanofibres. The alkali treatment was carried out using various concentrations of 2%, 4%, 8% and 16% of sodium hydroxide (NaOH) solution, while the bleaching treatment was carried out using sodium hypochlorite (NaClO) solution. The extraction of nano-fibrillated cellulose was achieved by means of acid hydrolysis with various concentrations of 5%, 15%, 30% and 60% sulphuric acid (H2SO4 ) under controlled conditions. The structural and functional groups were analysed using attenuated total reflection Fourier transform infra-red (ATR-FTIR) imaging, while a morphological analysis was performed using optical microscopy and transmission electron microscopy (TEM). The FTIR analysis indicated that the lignin, ink, fillers and other components had been removed after the alkali and bleaching treatments. The imaging analysis using an optical microscope showed that the extracted cellulose had a fibrous and rod-like structure, while the TEM images showed that the extracted cellulose ranged from micro to nano size down to ~20-30 nm depending on the concentration of acid used. The extraction of either micro-fibrillated or nano-fibrillated cellulose from office paper waste in this work might pave the way towards the alternative reuse of office paper waste for the production and application of cellulose materials. ************************************************************************ Peningkatan besar dalam penghasilan kertas dan selulosa, di mana kedua-dua sumber berasal dari pulpa kayu telah menyebabkan eksploitasi hutan yang teruk membawa masalah alam sekitar, iaitu penebangan hutan. Selain itu, pengurangan penggunaan kertas agak tidak seimbang. Oleh itu, berhubung dengan isu alam sekitar, pengambilan selulosa dari sisa kertas boleh menjadi inisiatif alternatif untuk mengurangkan kesan negatif melalui kitar semula sisa kertas. Dalam kajian ini, pengekstrakan selulosa mikrofibril dan nanofibril telah dicapai menggunakan bahan buangan kertas sebagai sumber. Rawatan alkali dan pelunturan digunakan untuk pengestrakan serat selulosa diikuti oleh kaedah hidrolisis asid yang terkawal untuk pengasingan selulosa nanofibril. Rawatan alkali dijalankan menggunakan pelbagai kepekatan 2%, 4%, 8% dan 16% natrium hidroksida (NaOH) manakala rawatan pelunturan dilakukan dengan menggunakan larutan natrium hipoklorit (NaClO). Pengekstrakan selulosa nanofibril dicapai dengan menggunakan kaedah hidrolisis asid yang terkawal dengan pelbagai kepekatan 5%, 15%, 30% dan 60% asid sulfurik (H2SO4 ). Analisa kumpulan struktur dan fungsi dianalisis dengan menggunakan pantulan keseluruhan dikecilkan spektroskopi infra-merah transformasi Fourier (ATR-FTIR) manakala pengimejan dan analisis morfologi diperiksa menggunakan mikroskop optik dan mikroskop elektron transmisi (TEM). Analisis FTIR menunjukkan lignin, dakwat, pengisi dan komponen lain dikeluarkan selepas rawatan alkali dan pelunturan. Analisa pengimejan menggunakan mikroskop optik menunjukkan struktur berserat dan rod seperti selulosa dapat diekstrak manakala imej TEM menunjukkan saiz selulosa yang diekstrak dari mikro ke saiz nano hingga ~20-30 nm bergantung kepada kepekatan asid yang digunakan. Pengekstrakan selulosa microfibril atau nanofibril dari sisa kertas pejabat dalam kajian ini mungkin membuka jalan ke arah penggunaan semula sisa kertas pejabat dalam pengeluaran dan aplikasi bahan selulosa.